Conduct disorders and psychopathy in children and adolescents: aetiology, clinical presentation and treatment strategies of callous-unemotional traits - Simone Pisano (Italian Journal of Pediatrics, 2017)
Abstract Conduct Disorder (CD) is a psychiatric diagnosis characterized by a repetitive and persistent pattern of behaviour in which the basic rights of others and major age-appropriate social norms or rules are violated. Callous Unemotional (CU) traits are a meaningful specifier in subtyping CD for more severe antisocial and aggressive behaviours in adult psychopathology; they represent the affective dimension of adult psychopathy, but they can be also detected in childhood and adolescence. The CU traits include lack of empathy, sense of guilt and shallow emotion, and their characterization in youth can improve our diagnostic, prognostic and therapeutic abilities. A strong genetic liability, in interaction with parenting and relevant environmental factors, can lead to elevated levels of CU traits in children. We pointed out that CU traits can be detected in early childhood, may remain stable along the adolescence, but a decrease following intensive and specialized treatment is possible. We here provide a narrative review of the available evidences on CU traits in three main domains: aetiology (encompassing genetic liability and environmental risk factors), presentation (early signs and longitudinal trajectories) and treatments.